Cantinflas, Patriota de la patria e Insurgente del detalle - Héctor Ruiz Rivas (Caravelle)
While Cantinflas is a well-established Mexican cinema icon, the reasons for his great popularity might not be so easily grasped. For he embodies far more than the typical Mexico City underdog and witty rogue the audience usually identifies him with. A survey of his first period films will enable us to discover a thorough irreverent and devastating cinematographic machine that delves deep into the foundations of long-established Western values -including language-, from both a Latin-American and a universal outlook.